A method for generating dynamic compression shear coupled stress loading on living cells - Xu, Dasen; Zhang, Nu; Wang, Sijie; Zhang, Pan; Li, Yulong; Yang, Hui (Frontiers in Bioengineering and Biotechnology, 2022)
Changes in the mechanical properties of single cells are related to the physiological state and fate of cells. The construction of cell constitutive equations is essential for understanding the material characteristics of single cells. With the help of atomic force microscopy, bio-image processing algorithms, and other technologies, research investigating the mechanical properties of cells during static/quasi-static processes has developed rapidly. A series of equivalent models, such as viscoelastic models, have been proposed to describe the constitutive behaviors of cells. The stress-strain relations under dynamic processes are essential to completing the constitutive equations of living cells. To explore the dynamic mechanical properties of cells, we propose a novel method to generate a controllable dynamical compression shear coupling stress on living cells. A CFD model was established to visualize this method and display the theories, as well as assess the scope of the application. As the requirements or limitations are met, researchers can adjust the details of this model according to their lab environment or experimental demands. This micro-flow channel-based method is a new tool for approaching the dynamic mechanical properties of cells.